2022
DOI: 10.2174/1871520621666210903130152
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro Evaluation of Isatin Derivatives as Potent Anti-Breast Cancer Agents against MCF-7, MDA MB 231, MDA-MB 435 and MDA-MB 468 Breast Cancers Cell Lines: A Review

Abstract: Introduction: Breast cancer (BC) is one of the most frequent malignancy and most common reasons of impermanence in women. The backbone of therapy for BC is principally chemotherapy, but due to its non-specific nature between normal cells and cancer cells and severe side effects are the main barriers in its therapy. So, there is an intense requirement for the enlargement of more efficacious, more specific and safer anti-BC agents. Objective: Isatin (IST) is an endogenous molecule which is a principal class of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…23a It can be conjectured that the reaction could proceed through an initial nucleophilic attack of the aniline (25) to one of the ester moieties of an alkyl-2ketomalonate (mesoxalic ester 26) in AcOH to provide the amide i. In turn, this intermediate could cyclize under the promotion of the electron pair of the nitrogen atom, to afford species ii, resulting from isomerization or a [1,3]-hydrogen shift that regenerates the aromatic ring. Subsequent treatment with aqueous 1 M KOH, would cause hydrolysis of the ester and triggers the decarboxylation of the 1,3-dicarbonyl intermediate iii to deliver the 3-hydroxyindolinone (iv).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23a It can be conjectured that the reaction could proceed through an initial nucleophilic attack of the aniline (25) to one of the ester moieties of an alkyl-2ketomalonate (mesoxalic ester 26) in AcOH to provide the amide i. In turn, this intermediate could cyclize under the promotion of the electron pair of the nitrogen atom, to afford species ii, resulting from isomerization or a [1,3]-hydrogen shift that regenerates the aromatic ring. Subsequent treatment with aqueous 1 M KOH, would cause hydrolysis of the ester and triggers the decarboxylation of the 1,3-dicarbonyl intermediate iii to deliver the 3-hydroxyindolinone (iv).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11 We also realized that certain 4-substituted isatins like 9 induce dopaminergic or D2-agonist activity useful for treating hypertension 12a and others such as 10 proved to be relevant inhibitors of enzyme CDK2. 12b As a result, we became interested in melosatin A (1), which is reminiscent of 7−10 and shares structural similarity with the substitution pattern of the carbocyclic ring of melovinone (5). Remarkably, being cooccurring metabolites, Kapadia et al suggested a plausible common biogenetic origin for 1 and 5.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Isatin, widely distributed in natural kingdom, is a well-known pharmacologically active scaffold [ 17 , 18 ]. Isatin hybrids possessed significant therapeutic effect on breast cancers including drug-resistant forms, good selectivity and low toxic side effects [ 19 , 20 ]. Recent studies demonstrated that DHA-isatin hybrids exhibited promising antiproliferative activity against both drug-sensitive and drug-resistant cancer cell lines [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies revealed that DHA‐isatin hybrids possessed potential antiproliferative activity against both drug‐sensitive and drug‐resistant breast cancer cell lines, revealing that rational design of DHA‐isatin hybrids may provide novel anti‐breast cancer candidates [21,22] . The structure–activity relationship illustrated that the linker between DHA and isatin was critical for the antiproliferative activity of DHA‐isatin hybrids, and hybrids with alkyl linkers were generally more active than the 1,2,3‐triazole tethered analogs [19,20] . Ester is easy to hydrolyze, so the ester tethered DHA‐isatin hybrids may could act as prodrugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the therapeutic efficacy of DHA is compromised owing to its inherent disadvantages such as poor stability and low aqueous solubility [17,18] . Isatin, an endogenous molecule, could act on various biological targets, and its derivatives possessed profound in vitro and in vivo efficacies against various cancers including drug‐sensitive and multidrug‐resistant breast cancers [19,20] . Accordingly, isatin is a fruitful matrix for the development of novel anti‐breast cancer agents.…”
Section: Introductionmentioning
confidence: 99%